Corrosion detection in steel bar: A time-frequency approach. (October 2019) - Majhi, Subhra; Mukherjee, Abhijit; George, Nithin V.; Uy, Brian
Abstract: This paper presents a new technique for discerning corrosion in steel bars using guided ultrasonic waves with an improved signal processing technique. A mild steel bar has been subjected to accelerated corrosion. Information concerning variation in spectral traits associated with the spread of corrosion has been discerned. Dispersion curves for the steel bar have been deduced to understand and correlate the observed change in time-frequency spectra with shift in predominant modes with spread of corrosion. Theoretical and measured mass loss in the steel rebar is used as physical parameters to evaluate corrosion. Tensile tests of corroded specimen have also been undertaken to measure the residual strength of the corroded bars. The superiority of the proposed signal processing technique in clearly discerning the state of corrosion has been demonstrated.